2009
DOI: 10.3177/jnsv.55.434
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of a Tertiary Sulfonium Compound, Dimethylsulfoniopropionate, in Green Sea Algae on Ehrlich Ascites Carcinoma-Bearing Mice

Abstract: SummaryThe saline and dimethylsulfoniopropionate (DMSP) solutions at 5, 10 and 20 m M were preliminarily injected intraperitoneally every other day into two control and three DMSP groups of mice ( n ϭ 8) for 2 wk and thereafter Ehrlich ascites-carcinoma (EAC) cells were peritoneally injected to one control and three DMSP groups of mice, leaving one control group without the EAC injection. Then, the body weight and survival time of all mice were examined over a long rearing time up to 300 d. All EAC-bearing mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Recently we found that oral supplementation with 10 mM DMSP solution nearly reinstated 3 0 -methyl-4-dimethylaminoazobenzene (3 0 -MeDAB)-induced liver cancers in rats at the 33rd week, 9) and that intraperitoneal (ip) administration of 10 and 20 mM DMSP solutions to Ehrlich ascites carcinoma (EAC)-bearing mice maintain high survival rate (50 and 63%) for up to 300 d without side effect. 10) In these experiments, DMSP was found to activate the delayed-type hypersensitive immune system in the cancerous animals. 9,10) Hence a comparison of the effects of DMSA, DMSP and MeMet (Fig.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Recently we found that oral supplementation with 10 mM DMSP solution nearly reinstated 3 0 -methyl-4-dimethylaminoazobenzene (3 0 -MeDAB)-induced liver cancers in rats at the 33rd week, 9) and that intraperitoneal (ip) administration of 10 and 20 mM DMSP solutions to Ehrlich ascites carcinoma (EAC)-bearing mice maintain high survival rate (50 and 63%) for up to 300 d without side effect. 10) In these experiments, DMSP was found to activate the delayed-type hypersensitive immune system in the cancerous animals. 9,10) Hence a comparison of the effects of DMSA, DMSP and MeMet (Fig.…”
mentioning
confidence: 99%
“…10) In these experiments, DMSP was found to activate the delayed-type hypersensitive immune system in the cancerous animals. 9,10) Hence a comparison of the effects of DMSA, DMSP and MeMet (Fig. 1A) on the carcinoma and the immune systems in EAC-bearing mice was made in this study.…”
mentioning
confidence: 99%
See 3 more Smart Citations